Development of Student Worksheets Based on Science, Technology, Engineering, and Mathematics on the Material of the Human Digestive System for Class XI High School Students - Selvia*, Selvia; Tambunan, Efrida Pima Sari (Universitas Syiah Kuala, 2024)
The reality in the field shows that teachers have not yet fully utilized learning media in conducting lessons, and the student worksheets (LKPD) developed by the teachers are also not yet optimal. The purpose of this study is to develop a STEM-based LKPD learning media that is worthy, practical, and effective in the teaching and learning process. Field tests of validation and reliability of assessment instruments were carried out at high school students. Tahfizil qur'an yayasan islamic center sumatera utara in june 2024 by class XI-IPA students with 35 respondents. The method used in this study is the research and development method with the ADDIE model. The stages of the ADDIE model are analysis (analyzing), namely analyzing the learning needs of students and teachers. The design stage (designing), namely designing the product. The development stage (developing), namely the realization of making LKPD using canva and validation (1 lecturer expert in learning media, 1 lecturer expert in subject matter and 1 expert field practitioner (biology teacher)). The implementation stage (implementing), namely applying the media to students so that they know the feasibility of the product, the practicality of the product and the effectiveness to determine the level of students conceptual understanding in using the product as a teaching material. Based on the results and discussion of STEM-based LKPD on the human digestive system for class XI high school students, it is known that the feasibility of the media is measured through the results of the media expert validation assessment, namely 91.57% (very worthy), material experts, namely 98,6% (very worthy) and field practitioner experts (biology teachers) namely 85% (very worthy). Then, the practicality of the media is measured using a student response questionnaire, namely 82.56% (very practical). Meanwhile, the effectiveness test of the N-gain score product is 0.82 with an N-gain value 0.7 in the high category and the treatment criteria using LKPD are effective.